ISSUES FACED BY THE AGING LESBIAN AND GAY COMMUNITY IN SRI LANKA (Proceedings of the International Conference on Social Sciences, 2024)
Homosexuals (lesbians and gays) are an important social sex group that garners national and international attention from a range of perspectives. The main purpose of this study is to examine the issues confronting Sri Lanka's aging lesbian and gay community. The study was based on a qualitative research design, and the snowball sampling method was used to identify respondents as older lesbians and gays, as they are one of the hidden groups in society. The qualitative sample consisted of 20 persons, including two lesbians (02) and eighteen (18) gay persons who were aged 60 years and over. The data were analyzed using thematic and content analysis. It is a notable characteristic that these respondents form friends far from their family, siblings, and parents. These friendships are between 3–4 people. As they are unmarried, they have lived alone because of separation from their parents, a lack of marriage, and a lack of children. They have become excluded from society because they have been marginalized, neglected, and hampered by it. It has been confirmed that 16 respondents suffer from financial shortages in old age because they do not save money or invest. In addition, lesbians are experiencing financial pressure due to lower incomes than gay men. Most respondents were found to have illnesses such as high cholesterol and diabetes. They know about sexually transmitted diseases, but a large proportion of them don't know how to prevent them. Another point raised is that healthcare providers suffer from discrimination when accessing health services. Lack of financial resources, lack of health insurance, economic insecurity, and discrimination are facing challenges in care, while 18 respondents identified a significant need for institutionalized care. According to the conclusions reached through the analysis, due to the social, economic, health, and care problems faced by this lesbian and gay elderly community, focus on institutional care and implement programs to educate the general public, health care professionals, and employees of public and private institutions about them and HIV prevention. And it is timely that this community is participating effectively in counseling programs.
Keywords: homosexuals; lesbian; gay; aging